Anti-aging and anti-inflammatory fulfilled through the delivery of supramolecular bakuchiol in ionic liquid - Beibei Lu; Zhenyuan Wang; Ying Xu; Yue Liu; Bo Ruan; Jichuan Zhang; Jianglin Zhang; Jiaheng Zhang; Tao Zhang (Supramolecular Materials)
Bakuchiol, as a derivative of retinol, has attracted attention due to its strong anti-aging ability on the skin. However, how to solve its irritability and low permeability is a challenge in the field of skin anti-aging. This study used matrine and lauric acid to prepare an ionic liquid to enhance transdermal permeability and solve irritation. The results of the monomer of bakuchiol showed that the ionic liquid-loaded bakuchiol significantly improved the skin permeability of bakuchiol and completely solved the problem of low irritation of bakuchiol. As a single component, its penetration rate is 4.17 times that of retinol and 3.48 times that of bakuchiol, therefore it has a stronger inflammation inhibition rate and collagen expression ability (increasing the expression of col 1a1a, col 1a1b, and col 1a2). As a substitute for retinol, bakuchiol has great potential in anti-aging applications.